Molecular Characterization of a Debilitation-Associated Partitivirus Infecting the Pathogenic Fungus Aspergillus flavus - Jiang, Yinhui; Wang, Jingxian; Yang, Bi; Wang, Qinrong; Zhou, Jianjiang; Yu, Wenfeng (Frontiers in Microbiology, 2019)
The opportunistic human pathogenic fungus Aspergillus flavus is known to be infected with mycoviruses. In this study, we report a novel mycovirus Aspergillus flavus partitivirus 1 (AfPV1) that was originally isolated from the abnormal colonial morphology isolate LD-3-8 of A. flavus. AfPV1 has spherical virus-like particles about 40 nm in diameter, and three double-stranded RNA (dsRNA) segments (dsRNA1, 2, and 3 with lengths of 1.7, 1.4, and 1.1 kbp, respectively) were packaged in the virions. dsRNA1, dsRNA2 and dsRNA3 each contained a single open reading frame and potentially encoded 62 kDa, 42 kDa and 32 kDa proteins, respectively. The dsRNA1 encoded protein shows similarity to the RNA-dependent RNA polymerase (RdRp) of partitiviruses, and the dsRNA2 product has no significant similarity to any other capsid protein in the GenBank databases, beside some homology with the hypothetical “capsid” protein of a few partitiviruses. The dsRNA3 encodes a protein with no similarity to any protein in the GenBank database. SDS-PAGE and polypeptide mass fingerprint-mass spectrum (PMF-MS) analyses indicated that the CP of the AfPV1 was encoded by dsRNA2. Phylogenetic analysis showed that the AfPV1 and relative viruses were found in an unclassified group inside the Partitiviridae family. AfPV1 seems to result in debilitation symptoms, but had no significant effects to murine pathogenicity. These findings provide new insights into the partitiviruses taxonomy and the interactions between viruses and A. flavus.